Kualitas Laporan Keuangan OPD: Peran Akuntansi Berbasis Akrual dan Pengendalian Internal - Hajrat Mahajani; Rio Monoarfa; Lukman Pakaya (Transbahasa, 2026)
This study aims to examine the effect of accrual-based accounting implementation and the Government Internal Control System (SPIP) on the quality of financial reports in Regional Apparatus Organizations (OPDs) of Gorontalo Province. A quantitative approach was employed using primary data collected through questionnaires distributed to 100 employees involved in financial administration and management activities across several OPDs in Gorontalo Province. The sampling technique applied was purposive sampling, while the sample size was determined using the Cochran formula. Data were analyzed using multiple linear regression with the assistance of SPSS version 23. The findings reveal that the implementation of accrual-based accounting has a positive and significant effect on the quality of financial reports. Furthermore, the Government Internal Control System was also found to have a positive and significant influence on financial report quality. Simultaneously, both independent variables significantly affect the quality of OPD financial reports. The coefficient of determination of 0.407 indicates that 40.7% of the variation in financial report quality can be explained by accrual-based accounting implementation and SPIP, while the remaining 59.3% is influenced by other factors outside the research model. These findings highlight the importance of strengthening accrual-based accounting practices and internal control systems to improve the quality, reliability, and accountability of public sector financial reporting.